(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Karenina T, Herlinda S, Irsan C, Pujiastuti Y. 2019. Abundance and species diversity of predatory arthropods inhabiting rice of refuge habitats and synthetic insecticide application in freshwater swamps in South Sumatra, Indonesia. Biodiversitas 20: 2375-2387. Rice cultivation in freshwater swamps in Indonesia is specific, among other things, there is no synthetic pesticide spraying and vegetable growing on rice field embankments. This specific cultivation technique can affect the abundance and diversity of rice-dwelling arthropods species. The study aimed to compare the abundance and species diversity of predatory arthropods inhabiting rice surrounded both by refugia and vegetables and by those being applied with synthetic insecticide in the rice field of freshwater swamps. This study used rice plots surrounded by refugia flower (Zinnia sp., Tagetes erecta, Cosmo caudatus, and Sesamum indicum); vegetables (Cucumis sativus, Vigna sinensis, Luffa acutangula, and Momordica charantia); untreated; and synthetic insecticide. Twenty-five herbivore species of 12 families, 34 spider species of 8 families, and 24 species of predatory insects of 12 families were found on rice during a planting season. The lowest herbivore population and spider abundance were found on synthetic insecticide sprayed rice and they were significantly different from those of refugia-rice plots. The most abundant spiders and predatory insects were found on rice surrounded by refugia and were not significantly different from those of rice surrounded by vegetables. The highest species diversity for spiders and predatory insects was found on rice surrounded by refugia, whereas the lowest species diversity was found on synthetic pesticide sprayed rice. Therefore, rice surrounded by refugia flowers and vegetables was the most appropriate for habitat and niche of predatory arthropods.